Exchange market pressure and monetary policies - Tey, Sheik Kyin; Lee, Chin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
High currency pressure in exchange market might bring adverse effect to the economy and inaccurate policy will exacerbate the pressure condition and transform the downturn of economies to full-blown crisis. In order to examine the accurate policy response for currency crisis in four countries, namely Indonesia, Korea, Malaysia and Philippines, Structural Vector Autoregression (VAR) estimation model is used. The results of SVAR suggested that the expansionary monetary policies help to reduce currency pressure. In addition, domestic credit is dominant tool of monetary policy for managing exchange market pressure.